Podlaska i Suwalska Brygada Kawalerii w walkach o wyjście z okrążenia niemieckiego we wrześniu 1939 r. - Kozłowski, Włodzimierz (Acta Universitatis Lodziensis. Folia Historica, 1984)
The Independent Operational Group „Narew" was established when in March 1939 the military threat of Third Reich became more pronounced. Its task was to defend the Narew-Biebrza line in order to protect the eastern wing of the army „Modlin" and the railway track Warszawa–Grodno. Defeat on the front line, and thus on the Narew river led to retreat of the group. Its 18th infantry division was defeated by the prevailing enemy forces, while the cavalry – despite big losses – broke through to the East and reached later General Franciszek Kleeberg's troops ending its combat operations on October 5, 1939 near Kock.